Low-temperature fast-curing phenolic resin adhesive as well as preparation method and application thereof
By adding Ru-FeP@GO micro/nano reactor and other components to the phenolic resin adhesive, rapid curing is achieved at low temperature, solving the problem of high curing temperature and long time of traditional phenolic resin adhesives, and improving production efficiency and Gluing performance reduces energy consumption and cost.
Patent Information
- Application Number
- CN202411609224.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Traditional phenolic resin adhesives have high curing temperature and long time in the artificial board industry, which affects production efficiency and product performance. The raw material petroleum-based phenol has high toxicity and high market price, resulting in large production energy consumption and high prices.
Using low-temperature fast-curing phenolic resin adhesive formulas, including phenol, formaldehyde, sodium hydroxide, Ru-FeP@GO micro/nano reactors, functional fillers, catalysts and plasticizers, promote phenolics through specific ratios and process steps. Rapid curing of resin reduces curing temperature and time.
It realizes rapid curing at low temperatures, reduces energy losses, improves production efficiency, enhances glue strength and mechanical properties, reduces formaldehyde emission and free phenol, simplifies the process and reduces production costs.
Smart Images

Figure CN119320612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic resin adhesives, in particular to a low-temperature fast-curing phenolic resin adhesive, a preparation method and application thereof. Background Art
[0002] Phenolic resin adhesives are widely used in outdoor furniture and wooden structures due to their excellent bonding properties, heat resistance and weather resistance. They are also known as "trialdehyde" adhesives in the wood industry, along with melamine formaldehyde resin adhesives and urea formaldehyde resin adhesives. With the transformation and rapid development of my country's economy, the output of outdoor wood products such as reconstituted wood and oriented strand board has increased year by year, and the consumption of phenolic resin adhesives has also continued to increase. However, the raw material of phenolic resin adhesives, petroleum-based phenol, is highly toxic and has a high market price, resulting in high prices for phenolic resin adhesives and their adhesive products. At the same time, phenolic resins have the disadvantages of high curing temperature and long curing time, which leads to low production efficiency and high production energy consumption. In addition, high-temperature hot pressing further increases the energy loss of enterprises. Therefore, the research and development of phenolic resin adhesives that can be quickly cured at medium and low temperatures is of great practical significance for reducing energy loss and improving production efficiency. Summary of the invention
[0003] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0004] Therefore, the purpose of the present invention is to provide a low-temperature fast-curing phenolic resin adhesive, a preparation method and its application, which overcomes the defects of traditional phenolic resin as wood adhesive in the prior art, such as high temperature and long time required for hot pressing in the industrial production of artificial boards, which affects production efficiency and product performance.
[0005] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0006] A low-temperature fast-curing phenolic resin adhesive comprising:
[0007] Phenol, formaldehyde, sodium hydroxide, water, Ru-FeP@GO micro / nanoreactor, functional filler, catalyst and plasticizer;
[0008] Among them, the mass ratio of phenol to formaldehyde is 1:1.9-2.8, the amount of sodium hydroxide added is 5-20% of the total mass of phenol and formaldehyde, the amount of water added is 20-50% of the total mass of phenol, formaldehyde and sodium hydroxide, the amount of Ru-FeP@GO micro / nano reactor added is 0.2-1.5% of the total mass of phenol and formaldehyde, the amount of functional filler added is 2-8% of the total mass of phenol and formaldehyde, the amount of catalyst added is 0.1-0.5% of the total mass of phenol and formaldehyde, and the amount of plasticizer added is 0.5-2% of the total mass of phenol and formaldehyde.
[0009] As a preferred embodiment of the low-temperature fast-curing phenolic resin adhesive described in the present invention, the functional filler is any one or more of sepiolite, wood fiber, mica flakes, basalt fiber, calcium carbonate, and graphite.
[0010] As a preferred embodiment of the low-temperature fast-curing phenolic resin adhesive described in the present invention, the plasticizer is any one or more of polyethylene glycol, polyvinyl alcohol, epoxidized soybean oil, castor oil, and waste cooking oil.
[0011] A method for preparing a low-temperature fast-curing phenolic resin adhesive, the specific steps are as follows:
[0012] S1. Weigh phenol, water and 40% sodium hydroxide solution, and stir at room temperature for 10 minutes to prepare a mixed solution;
[0013] S2, weigh 37% formaldehyde and add it to the mixed solution, heat it to 40°C and react for 30 minutes, continue to add Ru-FeP@GO micro / nano reactor, functional filler and plasticizer, and then heat it to 70°C and keep it warm for 1 hour;
[0014] S3. Continue to add 37% formaldehyde and 40% sodium hydroxide solution into the reactor, react at 70° C., cool to room temperature, add a catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0015] As a preferred embodiment of the method for preparing a low-temperature fast-curing phenolic resin adhesive according to the present invention, the specific preparation steps of the Ru-FeP@GO micro / nano reactor are as follows:
[0016] Graphene and ferric nitrate were dispersed in methanol and ultrasonicated, while C4H6N2 was dissolved in the methanol solution;
[0017] Then, C4H6N2 solution was dropped into the mixture of graphene and ferric nitrate and stirred at room temperature to obtain ZIF-67@GO;
[0018] It was dispersed with phytic acid and RuCl3 in deionized water and mixed evenly, and then an appropriate amount of NaBH4 was added to the above mixture and stirred for a period of time to obtain a Ru-FeP@GO micro / nano reactor.
[0019] As a preferred embodiment of the method for preparing a low-temperature fast-curing phenolic resin adhesive according to the present invention, the specific preparation steps of the catalyst are as follows:
[0020] MoO3, thioacetamide and urea are dissolved in water by a one-pot method, cellulose is added to the mixed solution, and the mixture is stirred thoroughly and placed in a hydrothermal reactor to react for a period of time;
[0021] After the reaction is completed, the obtained product is washed with anhydrous ethanol and deionized water by centrifugation until the pH value is 7, thereby obtaining a MoS2 / NC composite material;
[0022] MoS2 / NC was dispersed in TA solution at room temperature and exfoliated with the aid of ultrasound to obtain a few-layer or single-layer TA-MoS2 / NC nanosheet composite catalyst.
[0023] As a preferred embodiment of the method for preparing a low-temperature fast-curing phenolic resin adhesive according to the present invention, the cellulose is any one or more of cellulose derivatives such as bacterial cellulose, aminated cellulose, and carboxymethyl cellulose.
[0024] As a preferred embodiment of the method for preparing a low-temperature fast-curing phenolic resin adhesive according to the present invention, the TA solution has a concentration of any one of 2.5, 50, 100, and 200 mg / mL.
[0025] The invention discloses an application of a low-temperature fast-curing phenolic resin adhesive in wood processing and artificial boards.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The low-temperature fast-curing phenolic resin adhesive developed by the present invention has important practical significance for reducing energy loss and improving production efficiency.
[0028] 2. The process of modified phenolic resin adhesive is relatively complicated. The process of the present invention is simple, the curing temperature is low, and the bonding strength is high, which solves the technical problems existing in the prior art, such as slightly weak bonding strength, complex production process, high curing temperature and harsh reaction conditions.
[0029] 3. In the present invention, for different stages of the curing reaction of the phenolic resin adhesive, without affecting the bonding performance, a micro / nano reactor is used to promote the curing reaction of the phenolic resin adhesive, and at the same time, the mechanical properties, flame retardant properties, and anti-mildew properties of the phenolic resin adhesive can be enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below in combination with the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0031] Figure 1 The present invention is a flow chart of a method for preparing a low-temperature fast-curing phenolic resin adhesive. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0033] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0035] The present invention provides a low-temperature fast-curing phenolic resin adhesive, a preparation method and an application thereof, which overcome the defects of conventional phenolic resin as a wood adhesive in the prior art, such as high temperature and long time required for hot pressing in the industrial production of artificial boards, which affects production efficiency and product performance.
[0036] This low temperature fast curing phenolic resin adhesive includes:
[0037] Phenol, formaldehyde, sodium hydroxide, water, Ru-FeP@GO micro / nanoreactor, functional filler, catalyst and plasticizer;
[0038] Among them, the mass ratio of phenol to formaldehyde is 1:1.9-2.8, the amount of sodium hydroxide added is 5-20% of the total mass of phenol and formaldehyde, the amount of water added is 20-50% of the total mass of phenol, formaldehyde and sodium hydroxide, the amount of Ru-FeP@GO micro / nano reactor added is 0.2-1.5% of the total mass of phenol and formaldehyde, the amount of functional filler added is 2-8% of the total mass of phenol and formaldehyde, the amount of catalyst added is 0.1-0.5% of the total mass of phenol and formaldehyde, and the amount of plasticizer added is 0.5-2% of the total mass of phenol and formaldehyde.
[0039] The functional filler is any one or more of sepiolite, wood fiber, mica flakes, basalt fiber, calcium carbonate, and graphite, and the plasticizer is any one or more of polyethylene glycol, polyvinyl alcohol, epoxidized soybean oil, castor oil, and waste cooking oil.
[0040] like Figure 1 As shown, the preparation method of the low-temperature fast-curing phenolic resin adhesive comprises the following specific steps:
[0041] S1. Stir 100-200 g of phenol, 80-180 g of water and 50-150 g of sodium hydroxide (40% solution) at room temperature for 10-20 min to prepare a mixed solution;
[0042] S2, then add 100-300g of 37% formaldehyde to the mixed solution, heat it to 40-60°C and react for 30min; continue to add 2-5g of Ru-FeP@GO micro / nano reactor, 5-30g of functional filler, 1-10g of plasticizer, then heat it to 70-95°C and keep it warm for 1h;
[0043] S3. Continue to add 10-50 g of 37% formaldehyde and 5-20 g of sodium hydroxide (40% solution) into the reactor, react at 70-95° C. for 0.5-3 h, cool to room temperature, add 0.5-3 g of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0044] The specific preparation steps of the Ru-FeP@GO micro / nano reactor are as follows:
[0045] 50-200 mg of graphene (GO) and 0.5-2 g of ferric nitrate are dispersed in 50-180 ml of methanol and ultrasonically treated for 1-3 h. At the same time, 1-2.5 g of C4H6N2 solution is dropped into the mixture of GO and ferric nitrate, and stirred at 20-30 ° C for 1-3 h to obtain the first step reactant; then 100-300 mg of the first step product is dispersed in 20-100 ml of water with 1-3 g of phytic acid and 10-50 mg of RuCl3, stirred for 10-30 min to mix evenly, and then an appropriate amount of 5-20 ml of NaBH4 is added to the above mixture, and stirred for 2-4 h to obtain a Ru-FeP@GO micro / nano reactor. Preferably, ZIF-67 can be replaced by MOF, COF, ZIF and porous nanomaterials. Graphene can be replaced by two-dimensional sheet materials such as boron nitride, hydrotalcite, and montmorillonite.
[0046] The specific preparation steps of the catalyst are as follows:
[0047] First, 0.1-2g of MoO3, 0.2-2.5g of thioacetamide and 5-10g of urea are dissolved in water, 0.5-1g of cellulose (NC) is added to the mixed solution, and the mixed solution is fully stirred for 10-30min and then placed in a hydrothermal reactor at 150-200°C for reaction for 10-20h. After the reaction is completed, the obtained product is washed with anhydrous ethanol and deionized water by centrifugation until pH=7 to obtain a MoS2 / NC composite material. At 20-30°C, 1-2g of MoS2 / NC is dispersed in a certain concentration of tannin (TA) solution and assisted in its peeling under ultrasonic conditions to obtain a few-layer or single-layer TA-MoS2 / NC nanosheet composite catalyst. Preferably, the TA solution is any one of 2.5, 50, 100, and 200 mg / mL in concentration, and the cellulose is any one or more of cellulose derivatives such as bacterial cellulose, aminated cellulose, and carboxymethyl cellulose.
[0048] The invention also provides application of a low-temperature fast-curing phenolic resin adhesive in wood processing and artificial boards.
[0049] In order to test the performance of the antistatic formaldehyde-free adhesive prepared by the present invention, the following Examples 1-6 and Comparative Examples 1-6 are first provided.
[0050] Example 1
[0051] A method for preparing a low-temperature fast-curing phenolic resin adhesive comprises the following steps:
[0052] S1. Weigh 100 kg of phenol, 80 kg of water and 50 kg of sodium hydroxide (40% solution), and stir at room temperature for 10 min to prepare a mixed solution;
[0053] S2, weigh 100 kg of 37% formaldehyde and add it to the mixed solution, heat it to 40°C and react for 30 minutes; continue to add 2 kg of Ru-FeP@GO micro / nano reactor, 5 kg of functional filler, and 1 kg of plasticizer, then heat it to 70°C and keep it warm for 1 hour;
[0054] S3. Continue to add 10 kg of 37% formaldehyde and 5 kg of sodium hydroxide (40% solution) into the reactor, react at 70° C. for 0.5 h, cool to room temperature, add 0.5 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0055] Example 2
[0056] S1. Weigh 120 kg of phenol, 90 kg of water and 50 kg of sodium hydroxide (40% solution), and stir at room temperature for 15 min to prepare a mixed solution;
[0057] S2, weigh 150kg of 37% formaldehyde and add it to the mixed solution, heat it to 45℃ and react for 30min; continue to add 2.5kg of Ru-FeP@GO micro / nano reactor, 10kg of functional filler, and 2kg of plasticizer, then heat it to 75℃ and keep it warm for 1h;
[0058] S3. Continue to add 20 kg of 37% formaldehyde and 10 kg of sodium hydroxide (40% solution) into the reactor, react at 75° C. for 1 hour, cool to room temperature, add 1 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0059] Example 3
[0060] S1. Weigh 150 kg of phenol, 100 kg of water and 100 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0061] S2, weigh 180kg of 37% formaldehyde and add it to the mixed solution, heat it to 50℃ and react for 30min; continue to add 3kg of Ru-FeP@GO micro / nano reactor, 20kg of functional filler, and 5kg of plasticizer, then heat it to 80℃ and keep it warm for 1h;
[0062] S3. Continue to add 25 kg of 37% formaldehyde and 10 kg of sodium hydroxide (40% solution) into the reactor, react at 80° C. for 0.5 h, cool to room temperature, add 1.5 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0063] Example 4
[0064] S1. Weigh 180 kg of phenol, 150 kg of water and 120 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0065] S2, weigh 250kg of 37% formaldehyde and add it to the mixed solution, heat it to 55℃ and react for 30min; continue to add 4kg of Ru-FeP@GO micro / nano reactor, 25kg of functional filler, and 8kg of plasticizer, then heat it to 85℃ and keep it warm for 1h;
[0066] S3. Continue to add 30 kg of 37% formaldehyde and 15 kg of sodium hydroxide (40% solution) into the reactor, react at 85° C. for 0.5 h, cool to room temperature, add 2 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0067] Example 5
[0068] S1. Weigh 200 kg of phenol, 100 kg of water and 150 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0069] S2, weigh 250kg of 37% formaldehyde and add it to the mixed solution, heat it to 60℃ and react for 30min; continue to add 4.5kg of Ru-FeP@GO micro / nano reactor, 25kg of functional filler, and 10kg of plasticizer, then heat it to 90℃ and keep it warm for 1h;
[0070] S3. Continue to add 40 kg of 37% formaldehyde and 20 kg of sodium hydroxide (40% solution) into the reactor, react at 90° C. for 0.5 h, cool to room temperature, add 2.5 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0071] Example 6
[0072] S1. Weigh 200 kg of phenol, 180 kg of water and 150 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0073] S2, weigh 300 kg of 37% formaldehyde and add it to the mixed solution, heat it to 60°C and react for 30 minutes; continue to add 5 kg of Ru-FeP@GO micro / nano reactor, 30 kg of functional filler, and 10 kg of plasticizer, then heat it to 95°C and keep it warm for 1 hour;
[0074] S3. Continue to add 50 kg of 37% formaldehyde and 20 kg of sodium hydroxide (40% solution) into the reactor, react at 95° C. for 0.5 h, cool to room temperature, add 3 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0075] In order to detect the performance of the antistatic formaldehyde-free adhesive prepared by the present invention, the present invention also provides a comparative example.
[0076] Comparative Example 1
[0077] S1, weigh 94kg of phenol, 207kg of formaldehyde solution and 56kg of sodium hydroxide solution, add them into the reactor, and react at 65°C for 10min;
[0078] S2, continue to add 54kg formaldehyde solution and 24kg sodium hydroxide solution to the reactor, and react at 85°C for 3.5h;
[0079] S3. Add 13.5 kg of urea into the reactor, react at 85° C. for 30 min, and quickly cool to room temperature to obtain a traditional phenolic resin adhesive.
[0080] Comparative Example 2
[0081] S1. Weigh 100 kg of phenol, 80 kg of water and 50 kg of sodium hydroxide (40% solution), and stir at room temperature for 10 min to prepare a mixed solution;
[0082] S2, weigh 100kg of 37% formaldehyde and add it to the mixed solution, heat it to 40℃ and react for 30min; continue to add 5kg of functional filler and 1kg of plasticizer, then heat it to 70℃ and keep it warm for 1h;
[0083] S3. Continue to add 10 kg of 37% formaldehyde and 5 kg of sodium hydroxide (40% solution) into the reactor, react at 70° C. for 0.5 h, and cool to room temperature to obtain a low-temperature fast-curing phenolic resin adhesive.
[0084] Comparative Example 3
[0085] S1. Weigh 150 kg of phenol, 100 kg of water and 100 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0086] S2, weigh 180kg of 37% formaldehyde and add it to the mixed solution, heat it to 50℃ and react for 30min; continue to add 3kg of Ru-FeP@GO micro / nano reactor, 20kg of functional filler, and 5kg of plasticizer, then heat it to 80℃ and keep it warm for 1h;
[0087] S3. Continue to add 25 kg of 37% formaldehyde and 10 kg of sodium hydroxide (40% solution) into the reactor, react at 80° C. for 0.5 h, and cool to room temperature to obtain a low-temperature fast-curing phenolic resin adhesive.
[0088] Comparative Example 4
[0089] S1. Weigh 200 kg of phenol, 180 kg of water and 150 kg of sodium hydroxide (40% solution), and stir at room temperature for 20 min to prepare a mixed solution;
[0090] S2, weigh 300kg of 37% formaldehyde and add it to the mixed solution, heat it to 60℃ and react for 30min; continue to add 30kg of functional filler and 10kg of plasticizer, then heat it to 95℃ and keep it warm for 1h;
[0091] S3. Continue to add 50 kg of 37% formaldehyde and 20 kg of sodium hydroxide (40% solution) into the reactor, react at 95° C. for 0.5 h, cool to room temperature, add 3 kg of catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
[0092] Comparative Example 5
[0093] S1. Take 10 g corn stalks and add them into 100 g 0.7 mol / L sulfuric acid solution, react for 3 h at 130° C. and a stirring rate of 500 rpm to obtain a corn stalk hydrolyzate, add alkali to adjust to neutrality, and set aside;
[0094] S2, take 3.4g corn straw hydrolysate in step S1 and 175.7g 37% formaldehyde (the mass ratio of corn straw hydrolysate to formaldehyde is 1:19) and stir at room temperature for 10min to prepare a mixed solution; take two-thirds of the mixed solution, 94g phenol and 56g 8mol / L sodium hydroxide solution into a reactor, and react at 65°C for 10min;
[0095] S3. Continue to add the remaining mixed solution and 24 g of 8 mol / L sodium hydroxide solution into the reactor, and react at 85° C. for 3.5 h; add 13.5 g of urea into the reactor, react at 85° C. for 30 min, and quickly cool to room temperature to obtain a biomass-based phenolic resin adhesive.
[0096] Comparative Example 6
[0097] S1, respectively taking 94g of phenol, 7.3g of alkali lignin, 138.5g of 37% formaldehyde by mass and 83.7g of 8M NaOH solution; mixing lignin or nano-lignin with formaldehyde and stirring to form a mixture (in this embodiment, the proportion of lignin replacing formaldehyde is 5%);
[0098] S2, adding two-thirds of the total mass of the mixture to phenol, and adding two-thirds of the total mass of the alkaline substance as a catalyst, raising the temperature to 65° C., and stirring for 30 minutes;
[0099] S3, adding the remaining mixture and alkaline substance again, and then slowly raising the temperature to 95°C and keeping it constant for 4h;
[0100] S4, cooling to room temperature to prepare a lignin-based phenolic resin, and storing the prepared lignin-based phenolic resin at a temperature below 25°C.
[0101] The low-temperature fast-curing phenolic resin adhesives prepared in Examples 1 to 6 and the adhesives prepared in Comparative Examples 1 to 6 were used to prepare three-layer plywood, using poplar veneers with a moisture content of less than 10% and a size of 40 cm*40 cm*0.15 cm, and the preparation was carried out according to the following process:
[0102] Gluing: Gluing on both sides of the core board, the glue coating amount is 350-400g / m 2 ;
[0103] Pressing: pressure 1MPa, temperature 110-130℃, time 6 minutes.
[0104] According to the testing method of GB / T17657-1999 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", the formaldehyde emission, free phenol, bonding strength, curing temperature and gel time of the produced plywood products were tested. The test results are shown in Table 1.
[0105] Table 1 - Physical properties of low temperature fast curing phenolic resin adhesive
[0106]
[0107] As can be seen from Table 1, the low-temperature fast-curing adhesive of the present invention uses basic raw materials such as phenol, formaldehyde, sodium hydroxide and water, and chemically designs the molecular structure of the phenolic resin during the reaction by adding a micro / nano reactor, a functional filler, a catalyst and a plasticizer, so as to obtain a low-temperature fast-curing phenolic resin adhesive that is easy to apply, has excellent bonding performance and is low in formaldehyde or formaldehyde-free. The test results show that the three-layer plywood pressed using the adhesive of the present invention has excellent mechanical properties, and the bonding strength is 1.18-1.59MPa, which is better than the comparative example.
[0108] As shown in Table 1, compared with the plywood prepared by the low-temperature fast-curing phenolic resin adhesive prepared in Examples 1 to 6, the bonding strength gradually increases, and the curing temperature and gel time gradually decrease. It can be seen that with the addition of micro / nano reactors and catalysts, the phenolic resin adhesive can obtain better bonding performance, lower curing temperature and shorter gel time.
[0109] Compared with the plywood pressed by the adhesive prepared in Example 1 and Comparative Example 2, the formaldehyde emission and free phenol are lower. This is because the addition of micro / nano reactors and catalysts to promote the reaction of phenolic resin allows raw materials such as phenol and formaldehyde to be efficiently utilized and fully react to form a stable chemical structure, thereby improving the bonding performance.
[0110] Compared with Example 1, Comparative Example 2 did not add a micro / nano reactor and a catalyst, and the plywood bonding strength was greatly reduced, and the free phenol and free formaldehyde contents increased significantly. Compared with Example 1, Comparative Example 3 did not add a micro / nano reactor, and the plywood bonding strength, free formaldehyde, and free phenol changed slightly, while the hot pressing temperature and gel time changed greatly. This is because the micro / nano reactor can participate in the synthesis reaction of the resin in the reaction system, and a coordination reaction occurs between the reactants to generate a chelate, thereby increasing the ratio of ortho-hydroxymethylphenol / para-hydroxymethylphenol and promoting the formation of a stable cross-linked structure.
[0111] Compared with Comparative Example 3 and Comparative Example 4, the gel time of the adhesive is reduced. This is because during the hot pressing curing stage of the phenolic resin adhesive, the catalyst can interact with the two hydroxyl groups between two adjacent resin molecules to transfer electron clouds, forming methylene bonds and dimethyl ether bonds, thereby promoting the curing reaction and reducing the gel time of the phenolic resin adhesive.
[0112] Compared with Comparative Example 5 (Patent Publication No.: CN116285804A Technical Solution of Example 1) and Comparative Example 6 (Patent Publication No.: CN110903446A Technical Solution of Example 1), the plywood pressed by the phenolic resin adhesive prepared by the present invention using a micro / nano reactor and a catalyst has formaldehyde release, free phenol, bonding strength, curing temperature and gel time, which are significantly superior to the existing invention technology.
[0113] Therefore, the preparation method of the low-temperature fast-curing adhesive of the present invention uses basic raw materials such as phenol, formaldehyde, sodium hydroxide and water, and chemically designs the molecular structure of the phenolic resin during the reaction by adding a micro / nano reactor, a functional filler, a catalyst and a plasticizer, so as to obtain a low-temperature fast-curing phenolic resin adhesive that is easy to apply, has excellent bonding performance and is low in formaldehyde or formaldehyde-free. The bonding strength of plywood is also higher than the national standard, and the adhesive has a good application prospect.
[0114] Although the present invention has been described above with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A low temperature fast curing phenolic resin adhesive, characterized in that: include: Phenol, formaldehyde, sodium hydroxide, water, Ru-FeP@GO micro / nanoreactor, functional filler, catalyst and plasticizer; Among them, the mass ratio of phenol to formaldehyde is 1:1.9-2.8, the amount of sodium hydroxide added is 5-20% of the total mass of phenol and formaldehyde, the amount of water added is 20-50% of the total mass of phenol, formaldehyde and sodium hydroxide, the amount of Ru-FeP@GO micro / nano reactor added is 0.2-1.5% of the total mass of phenol and formaldehyde, the amount of functional filler added is 2-8% of the total mass of phenol and formaldehyde, the amount of catalyst added is 0.1-0.5% of the total mass of phenol and formaldehyde, and the amount of plasticizer added is 0.5-2% of the total mass of phenol and formaldehyde.
2. A low temperature fast curing phenolic resin adhesive according to claim 1, characterized in that: The functional filler is any one or more of sepiolite, wood fiber, mica flakes, basalt fiber, calcium carbonate and graphite.
3. A low temperature fast curing phenolic resin adhesive according to claim 1, characterized in that: The plasticizer is any one or more of polyethylene glycol, polyvinyl alcohol, epoxidized soybean oil, castor oil, and waste cooking oil.
4. A method for preparing a low-temperature fast-curing phenolic resin adhesive as claimed in any one of claims 1 to 3, characterized in that: The specific steps are as follows: S1. Weigh phenol, water and 40% sodium hydroxide solution, and stir at room temperature for 10 minutes to prepare a mixed solution; S2, weigh 37% formaldehyde and add it to the mixed solution, heat it to 40°C and react for 30 minutes, continue to add Ru-FeP@GO micro / nano reactor, functional filler and plasticizer, and then heat it to 70°C and keep it warm for 1 hour; S3. Continue to add 37% formaldehyde and 40% sodium hydroxide solution into the reactor, react at 70° C., cool to room temperature, add a catalyst, and obtain a low-temperature fast-curing phenolic resin adhesive.
5. The method for preparing a low-temperature fast-curing phenolic resin adhesive according to claim 4, characterized in that: The specific preparation steps of the Ru-FeP@GO micro / nano reactor are as follows: Graphene and ferric nitrate were dispersed in methanol and ultrasonicated, while C4H6N2 was dissolved in the methanol solution; Then, C4H6N2 solution was dropped into the mixture of graphene and ferric nitrate and stirred at room temperature to obtain ZIF-67@GO; It was dispersed with phytic acid and RuCl3 in deionized water and mixed evenly, and then an appropriate amount of NaBH4 was added to the above mixture and stirred for a period of time to obtain a Ru-FeP@GO micro / nano reactor.
6. The method for preparing a low-temperature fast-curing phenolic resin adhesive according to claim 4, characterized in that: The specific preparation steps of the catalyst are as follows: MoO3, thioacetamide and urea are dissolved in water by a one-pot method, cellulose is added to the mixed solution, and the mixture is stirred thoroughly and placed in a hydrothermal reactor to react for a period of time; After the reaction is completed, the obtained product is washed with anhydrous ethanol and deionized water by centrifugation until the pH value is 7, thereby obtaining a MoS2 / NC composite material; MoS2 / NC was dispersed in TA solution at room temperature and exfoliated with the aid of ultrasound to obtain a few-layer or single-layer TA-MoS2 / NC nanosheet composite catalyst.
7. The method for preparing a low-temperature fast-curing phenolic resin adhesive according to claim 6, characterized in that: The cellulose is any one or more of cellulose derivatives such as bacterial cellulose, aminated cellulose, and carboxymethyl cellulose.
8. The method for preparing a low-temperature fast-curing phenolic resin adhesive according to claim 6, characterized in that: The TA solution has a concentration of 2.5, 50, 100, or 200 mg / mL.
9. Use of a low-temperature fast-curing phenolic resin adhesive as claimed in any one of claims 1 to 3 in wood processing and artificial boards.
Citation Information
Patent Citations
Method for preparing lignin-based phenolic resin by replacing formaldehyde with lignin
CN110903446A
Epoxidized soybean oil modified phenolic resin as well as preparation method and application thereof
CN106432655A
Nano wave-absorbing particle modified phenolic resin adhesive and preparation method thereof
CN114106754A
Preparation method of phenolic resin
CN114685742A
Biomass-based phenolic resin adhesive and preparation method thereof
CN116285804A